Implementasi Low Power System Pada Protokol Universal Plug and Play (UPnP) Pada Sensor dan Aktuator Untuk Otomasi Lampu - Surya Nur Ardiansah; Mochammad Hannats Hanafi Ichsan; Agung Setia Budi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Smart home becomes popular topic right now, with smart home, the human daily work becomes easier and more effective. Smart home can control or command an object that has been programmed to do a certain activity. There are problems while we use smart home based on the electric power and the number of components used on smart home. The low power system method is used in this study is to efficient the use of electric power by minimizing the resources that are not used in the software-level system. This efficiency is achieved by turning off services that are not used until the basic lowest point of the system can work normally. The UPnP protocol was chosen because of its flexible nature. Since there are plenty of smart home components, it takes numerous control and configuration on each component to connect between each other. Therefore, UPnP addressing and delivery-description can solve the problems. With this feature, it is possible to make the system connected without any manual configuration (zeroconf). The author uses the Raspberry Pi microcontroller as a center for information processing, motion sensors (PIR) and light intensity sensors (LDR) as input data for the system, and a lamp as an actuator. The Control points can searching, receiving, and governing each component in the system. By using the low power system method, each device (PIR Sensor, LDR Sensor, Control Point) can reach the point of efficiency in 38.25%, 37.61%, and 30.85%. Due to reduce the resources used, there are consequences on adding a delay which was originally an average of 374.46ms to 732.77ms or a difference of 33.8%.